Pamor Blackberry Messenger Terhadap Efektivitas Komunikasi Staff Notaris Dan PPAT - Zakrimal Zakrimal (Universitas Putera Batam, 2014)
The effectiveness of communication is a form of communication that is expected to have a shorter process, solid, and clear and give a satisfactory result according to what is desired. With effectiveness, communication is expected to be easily shared, of course, with the help of advances in technology today, one of which is the availability of Blackberry Messenger. For users of BlackBerry Messenger can be used for communication employees on the job or communications that are not related to work, given the cost is quite cheap. The purpose of this study was to determine and obtain a prestige tentangt Blackberry Messenger to effective staff communication Notary and PPAT Batam so that the use of communications technology is not only used as a trend of life. The method used in this study is a quantitative approach, using descriptive study aimed to solve the problem by exposing or describe conditions that are happening today.